THE ETHICS OF BANKING: ANALYSIS AND ESTIMATES - Jasevičienė, Filomena (Ekonomika, 2012)
With the banking business developing, the system of bank values is becoming increasingly relevant. Adherence to the norms of the bank’s ethics helps developing and improving ties among the bank’s employees as well as relations with the clients. Appropriate behaviour and social culture on the part of the staff shape the image of the bank and stimulate loyalty in the clients. The sophisticated and reliable operation of banks can be judged both in terms of its legal and economic aspects, and ethics. The article addresses the ethics requirements for banks’ staff, deals with the analysis and assessment of the application of ethical norms in the process of rendering financial services, and reveals the principal provisions laid down in banks’ codes of ethics and estimations.